Multidisciplinary management of a rare case of a large functional paraganglioma in the posterior mediastinum in an adolescent: a case report and literature review - Liao, Li Hang; Du, Xiao Jun; Ma, Jian; Ren, Zhang Yong (Frontiers in Oncology, 2025)
A pheochromocytoma (PPGL) in the mediastinum can originate from the paravertebral sympathetic nerve chain in the posterior mediastinum, or from the intervertebral, subclavian, coronary, pulmonary, or paravertebral paraganglia in the anterior or middle mediastinum. This case report presents the diagnosis of a large, functional paraganglioma in the posterior mediastinum, accompanied by excessive catecholamine secretion, in a 14-year-old male patient. Through multidisciplinary collaboration, radical tumor resection was performed with successful outcomes. This study systematically summarizes the standardized diagnostic pathway and key surgical techniques for this rare disease. The patient exhibited symptoms of exercise-induced retrosternal pressure and paroxysmal palpitations. A chest CT scan prior to surgery revealed a large tumor in the posterior mediastinum, measuring 8.0 × 5.6 × 7.2 cm, which was wrapping around the descending aorta. During the surgical procedure, it was demonstrated that an acute hypertensive crisis was precipitated by the presence of tumor traction and compression. Despite rigorous pharmacological intervention, blood pressure levels were highly variable (ranging from 235/172 mmHg to 36/26 mmHg). Subsequent pathological analysis after surgery confirmed the diagnosis of a functional paraganglioma, as indicated by strong positive CgA expression as determined by immunohistochemical staining. This case study provides a detailed account of managing a posterior mediastinal paraganglioma, emphasizing the dual challenges of diagnosis and treatment. The first challenge is definitively determining the patient’s functional status through multimodal imaging combined with biomarkers. The second is optimizing an α-receptor blockade regimen and developing dynamic blood flow management strategies intraoperatively to prevent life-threatening complications.